APPLICATION OF A PARTICLE SWARM OPTIMIZATION IN AN OPTIMAL POWER FLOW - D. Ben Attous (Journal of Fundamental and Applied Sciences, 2010)
In this paper an efficient and Particle Swarm Optimization (PSO) has been presented for solving the economic dispatch problem. The objective is to minimize the total generation fuel and keep the power outputs of generators; bus voltages and transformer tap setting in their secure limits. The conventional load flow and incorporation of the proposed method using PSO has been examined and tested for standard IEEE 30 bus system. The PSO method is demonstrated and compared with conventional OPF method (NR, Quasi Newton), and the intelligence heuristic algorithms such ac genetic algorithm, evolutionary programming. From simulation results it has been found that PSO method is highly competitive for its better general convergence performance.